Vegetation Analysis and Carbon Sequestration Potential of Salix alba Plantations under Temperate Conditions of Kashmir, India - Shah, Murtaza; Masoodi, T. H.; Khan, P. A.; Wani, J. A.; Mir, S. A. (Indian Forester, 2015)
The present study was conducted in Anantnag, Bandipora, Baramulla and Ganderbal districts of J.&K. After reconnaissance, survey was conducted and two plantation blocks of willow were selected in each district. Analysis of the data revealed that Salix albawas the dominant species with individualistic density of 81.90 % and IVI of 213.80. The existing stem volume, biomass production, carbon density and carbon sequestration potential of trees at all the selected locations were evaluated. The maximum and minimum stem volume of 739.34 and 595.09 cum ha-1 was recorded at Bandipora and Anantnag districts. The biomass production varied from 429.27 Mg ha-1 in Anantnag to 532.61 t ha-1 in Bandipora. The maximum soil carbon density of 68.07 t ha-1 was recorded at Bandipora, followed by 67.93 t ha-1 at Baramulla, 66.86 t ha-1 at Ganderbal and 66.43 t ha-1 at Anantnag.